Simple ways to calculate stable isotope discrimination factors and convert between tissue types. Issue 11 (15th July 2015) - Greer, Amanda L.; Horton, Travis W.; Nelson, Ximena J.
Summary: Traditional methods to determine stable isotope discrimination factors (Δ) between an animal's diet and tissue(s) are costly and time‐consuming. Consequently, data are only available for relatively few species and are completely absent from some orders, including parrots (Order: Psittaciformes). We present simple and cost‐effective methodologies for establishing discrimination factors and converting between tissue types. We investigated Δ 13 Cdiet‐feather and Δ 15 Ndiet‐feather values for the kea parrot Nestor notabilis by comparing the isotope values from feathers of a population held under their regular conditions at a local zoo, with the δ 13 C and δ 15 N values from their weekly diet of >30 food items. We mathematically controlled for dietary elemental concentration, and the potential impacts of metabolic routing, the exclusive consumption of preferred foods and the large‐scale consumption of self‐sourced plants and invertebrates, resulting in Δ 13 Cdiet‐feather = 4·00‰ ± 0·03 and Δ 15 Ndiet‐feather = 3·10‰ ± 0·20. We also determined regression equations for predicting feather δ 13 C and δ 15 N values from whole blood values by sampling simultaneously grown feathers and blood from wild kea nestlings. These are the first feather–blood discrimination equations determined for terrestrial birds in the wild. Our δ 13 C feather–blood discrimination equation was similar to an equation developed for use across marine birds; however, the δ 15 N feather–blood discrimination equation for marine birds consistently underestimated kea feather δ 15 N values. These methodologies, while developed for use in birds, can easily be applied to other animal classes given the appropriate selection of tissues.